Ion Beam Induced Charge analysis of diamond diodes - Lehnert, J.; Meijer, J.; Ronning, Carsten; Spemann, D.; Vittone, Ettore (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2017)
Diamond based p-i-n light-emitting diodes, developed to electrically drive single-photon sources in the visible spectral region at room temperature, have the potential to play a key role in quantum based technologies. In order to gain more insight into the charge injection mechanism occurring in these diodes, we carried out an experiment aimed to investigate the electrostatics and the charge carrier transport by the Ion Beam Induced Charge (IBIC) technique, using 1 MeV He microbeam raster scanning of p-i-n structures fabricated in a high purity diamond substrate, using lithographic masking and P and B ion implantation doping. Charge Collection Efficiency (CCE) maps obtained at low ion fluence, show that induced charge pulses arise only from the P-implanted region, whereas no IBIC signals arise from the B-implanted region. This result suggests the formation of a slightly p-type doped substrate, forming a n+-p-p+, rather than the expected p-i-n, structure. However, for high fluence scans of small areas covering the intrinsic gap, CCE maps are more uniform and compatible with a p-i-n structure, suggesting the occurrence of a “priming effect”, which saturates acceptor levels resulting in a decrease of the effective doping of the diamond substrate.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Diamond diodes; Electroluminescence; Ion Beam Induced Charge (IBIC) technique; Luminescent centers in diamond